The Relationship Between The Implementation Of The Problem Based Learning Model And Students’ Active Participation In Islamic Religious Education Learning In Grade XI Of SMK YASPI Labuhan Deli - Hirzi, Nadhil (Yayasan Rahmat Islamiyah, 2026)
This study aims to determine the relationship between the implementation of the Problem Based Learning (PBL) model and students’ active participation in Islamic Religious Education (IRE) learning in Grade XI of SMK YASPI Labuhan Deli. Students’ active participation is one of the important indicators of successful learning, emphasizing students’ cognitive, affective, and psychomotor involvement. The PBL model was chosen because it positions students as the center of learning through contextual and meaningful problem-solving activities. This research employed a quantitative approach using a correlational method. The population of this study consisted of all Grade XI students of SMK YASPI Labuhan Deli, with the sample determined using an appropriate sampling technique. Data were collected through questionnaires measuring the implementation of the PBL model and students’ active participation. Data analysis was conducted using statistical correlation techniques. The results indicate that there is a positive and significant relationship between the implementation of the Problem Based Learning model and students’ active participation in Islamic Religious Education learning. These findings suggest that the better the implementation of the PBL model, the higher the level of students’ active participation in the learning process. Therefore, the Problem Based Learning model is recommended as an effective alternative learning model to enhance students’ active participation in Islamic Religious Education.